Investing in flood protection in Asia: An empirical study focusing on the relationship between investment and damage - Mikio Ishiwatari (Elsevier, 2021)
Investing in disaster risk reduction is crucial in achieving the Sustainable Development Goals since natural disasters can impede sustainable development by causing economic and human losses. To consider investment in disaster risk reduction, policymakers need information on appropriate scales of investment depending on disaster damage occurred and socioeconomic development. However, there is a limited number of empirical studies that examine investment in disaster risk reduction, since the dataset of investments across countries is rarely available. This study aims at proposing the approaches of financing investment in flood protection, which is integrated with climate change adaptation. To our knowledge, this study is the first empirical analysis on the relationship between investment and damage and socio-economic development across economies. A multiple regression model is applied to analyze the relationship between investment in flood protection and flood damage and other socio-economic development. Investment data were collected from government agencies in major flood-prone countries in Asia. It was found that greater flood damage is associated with a larger budget for flood protection. The governments start increasing budgets after major disasters happen and further increase them as GDP per capita and population density rise. To study investment in disaster risk reduction further, datasets of budgets need to be established.